Pelvic floor muscle exercises alleviate symptoms and improve mental health and rectal function in patients with low anterior resection syndrome - Yuanyuan, Wu; Shiyin, He; Lei, He; Ding, Ding (Frontiers in Oncology, 2023)
Background: Pelvic floor rehabilitation has been reported to be effective in improving fecal incontinence. The aim of this study was to evaluate the effectiveness of combined pelvic floor muscle exercises (PFME) and Loperamide treatment on rectal functions and mental health prospectively for low anterior resection syndrome (LARS) patients after sphincter-saving operations (SSO) for rectal cancer. Methods: A total of 60 inpatients diagnosed with LARS were enrolled and randomly assigned into two groups: patients in Group A(n=30) treated with PFME intervention and Group B(n=30) with control condition for 4 weeks. High-resolution anorectal manometry (HRAM) was performed for all LARS patients to record HRAM parameters. The demographic information of all patients was collected before they completed several questionnaires, including the Hospital Anxiety and Depression Scale (HADS), the Wexner score, stool frequency per day, and Bristol Stool Form Scale (BSFS). Results: No significant differences in baseline data was observed. With regard to rectal functions, we found significant improvements in maximal resting pressure (MRP) (39.93±5.02mmH2O vs. 28.70±5.40mmH2O, P<0.001) and maximal squeeze pressure (MSP) (132.43±8.16mmH2O vs. 113.33±9.87mmH2O, P<0.001) of Group A patients whe compared to those of Group B at week 4. Meanwhile, Wexner score was significantly lower in Group A than that in Group B at week 4 (8.10 ± 1.24 vs. 9.87 ± 1.29 ml, P=0.018). Meanwhile, stool frequency (6.47±0.90 vs. 7.83±0.93, P<0.001) and BSFS (5.17±0.65 vs. 6.10±0.80, P=0.020) were significantly lower in Group A than those in Group B at week 4. Notably, HADS was significantly lower in Group A than that in Group B at week 4 (8.25 ± 2.36 vs. 10.48 ± 3.01, P<0.001). Meanwhile, anxiety score (4.16±1.38 vs. 5.33±1.69, P<0.001) and depression score (4.09±1.56 vs. 5.15±1.89, P<0.001) were significantly lower in Group A than those in Group B at week 4. Conclusion: Pelvic floor muscle exercises are effective treatment and ameliorate symptoms, rectal functions and mental health in patients with low anterior resection syndrome.